Heterogeneous addiction to transforming growth factor‐beta signalling in recessive dystrophic epidermolysis bullosa‐associated cutaneous squamous cell carcinoma. (9th October 2020) - Dayal, J.H.S.; Mason, S.M.; Salas‐Alanis, J.C.; McGrath, J.A.; Taylor, R.G.; Mellerio, J.E.; Blyth, K.; South, A.P.; Inman, G.J.
Summary: Background: Recessive dystrophic epidermolysis bullosa (RDEB) is associated with a high mortality rate due to the development of life‐threatening, metastatic cutaneous squamous cell carcinoma (cSCC). Elevated transforming growth factor‐beta (TGF‐β) signalling is implicated in cSCC development and progression in patients with RDEB. Objectives: To determine the effect of exogenous and endogenous TGF‐β signalling in RDEB cSCC with a view to assessing the potential of targeting TGF‐β signalling for RDEB cSCC therapy. Methods: A panel of 11 patient‐derived RDEB cSCC primary tumour keratinocyte cell lines (SCCRDEBs) were tested for their signalling and proliferation responses to exogenous TGF‐β. Their responses to TGF‐β receptor type‐1 (TGFBR1) kinase inhibitors [SB‐431542 and AZ12601011 (AZA01)] were tested using in vitro proliferation, clonogenicity, migration and three‐dimensional invasion assays, and in vivo tumour xenograft assays. Results: All SCCRDEBs responded to exogenous TGF‐β by activation of canonical SMAD signalling and proliferative arrest. Blocking endogenous signalling by treatment with SB‐431542 and AZ12601011 significantly inhibited proliferation (seven of 11), clonogenicity (six of 11), migration (eight of 11) and invasion (six of 11) of SCCRDEBs. However, these TGFBR1 kinase inhibitors also promoted proliferation and clonogenicity in two of 11 SCCRDEB cell lines. Pretreatment of in vitro TGFBR1‐addicted SCCRDEB70 cells with SB‐431542 enhanced overall survival and reduced tumour volume in subcutaneous xenografts but had no effect on nonaddicted SCCRDEB2 cells in these assays. Conclusions: Targeting TGFBR1 kinase activity may have therapeutic benefit in the majority of RDEB cSCCs. However, the potential tumour suppressive role of TGF‐β signalling in a subset of RDEB cSCCs necessitates biomarker identification to enable patient stratification before clinical intervention. Abstract : What is already known about this topic? Canonical transforming growth factor‐beta (TGF‐β) signalling is active in skin and cutaneous squamous cell carcinoma (cSCC) tumours of patients with recessive dystrophic epidermolysis bullosa (RDEB) but its role in tumorigenesis is unknown. There is no evidence of mutational inactivation of canonical TGF‐β signalling in RDEB cSCC. What does this study add? Exogenous TGF‐β stimulation of patient‐derived RDEB cSCC tumour cells (PDTCs) activates canonical signalling and inhibits cell proliferation in all samples in vitro . Inhibition of endogenous TGF‐β signalling inhibits proliferation, clonogenicity, migration and invasion in the majority of PDTCs but can also have no effect or promote proliferation and clonogenicity in some PDTCs. What is the translational message? Endogenous TGF‐β signalling has potential tumour‐promoting effects in the majority of RDEB cSCCs but may also have tumour‐suppressing effects in some samples. TGF‐β signalling is an attractive potential therapeutic target in many but not all RDEB cSCCs. Biomarkers for TGF‐β addiction need to be developed for patient stratification. Linked Comment: Guttmann‐Gruber and Piñón Hofbauer. Br J Dermatol 2021; 184 :592–593 .